Enhanced impurity removal of ionic rare earth leaching solution through the use of lauryl glucoside. (15th May 2022) - Luo, Xianping; He, Kunzhong; Zhou, Hepeng; Zhang, Yongbing; Xie, Fanxing
Graphical abstract: Highlights: Lauryl glucoside was the first time used in an ionic rare earth leaching solution. No ammonia nitrogen was produced compared to NH4 HCO3 when LG was used. LG has a high-efficiency impurity removal effect when compared with NH4 HCO3 . In pH 5.4, HCO3 – and CO3 2– produced by NH4 HCO3 which caused the loss of earth rare. A new Al-O bond was formed by LG and wouldn't lose rare earth while removing Al 3+ . Abstract: Lauryl glucoside (LG) was used for the first time as an impurity removal agent in ionic rare earth leaching solution to strengthen the removal of impurity metal ions and avoid the loss of rare earth effectively. Compared with ammonium bicarbonate (NH4 HCO3 ), LG can ensure the high efficiency of impurity removal while avoiding ammonia nitrogen pollution. The impurity removal test showed that 91.03 ± 0.1% aluminum ion (Al 3+ ) removal rate, 92.53 ± 0.2% iron ion (Fe 3+ ) removal rate, and 23.27 ± 1.3% rare earth (Re 3+ ) loss rate could be obtained when NH4 HCO3 was used to adjust the pH value of leaching solution to 5.4. But the 99.09 ± 1.9% Al 3+, 93.13 ± 1.3% Fe 3+ removal rates, 5.33 ± 0.9% rare earth loss rate could be obtained by using LG as impurity remover. Infrared spectroscopy and solution chemical calculation showed that NH4 HCO3 reacted with impurity metal ions to form Al(OH)3 precipitate, and a large amount of carbonate rare earth was formed. However, when LG was used as impurity remover, LG reacted with impurity metal ions to form a new Al-O band and no absorption peak related to rare earth ions that was found in the infrared spectrum. Density functional theory (DFT) calculation showed that at pH 5.4, the interaction intensity between LG and Al(OH)3 was largest, and rare earth ions did not interact with it. As the pH value of the leaching solution gradually exceeds 5.2, the free rare earth ions changed into the form of rare earth hydroxide. It caused the interaction between LG and rare earth elements to increase, resulting in the loss of rare earth. In addition, LG, as a green surfactant derived from renewable plant raw materials, could degrade naturally without causing environmental pollution. Therefore, using LG as an impurity remover can have a good application prospect in strengthening the impurity removal of ionic rare earth leaching solution.